Telling and selling; Literary fiction in early Malay language newspapers in colonial Indonesia - Nieβ, Joachim (UI Scholars Hub, 2016)
When newspapers in the colloquial Malay language appeared in the Dutch East Indies in the middle of the nineteenth century, they did more than just publish news reports and advertisements. They also created a new platform for the telling and distribution of literary fiction. In effect, literary texts soon played an important role in the vernacular print media. The first part of this article analyses the attraction of newspaper literature from the perspective of both the reader and the editor in general and gives a survey of the various forms of literary genres which can be found in newspapers in the late nineteenth and early twentieth century. In the second part, one particular serialized novel will be discussed in detail to demonstrate how the mode of publication also influenced the way stories were told.